PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PEMOHON SIM DAN SKCK DI POLRESTA MATARAM - Refindo Pradikta Rulando; M Ikhsan; Nurmala Pangaribuan (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Driving license and Police certificate services carried out by the Mataram City Resort Police in their daily implementation try to provide excellent service with an emphasis on applicant satisfaction. Therefore, this study aims to analyze and determine the level of service quality to the satisfaction level of driving license and police certificate applicants at the Mataram city resort police. The study used a survey method which was conducted by giving a questionnaire to 1302 respondents in the first semester of 2021. The data collection technique using this questionnaire has been tested for validity and reliability.The results from 1302 respondents revealed that the analysis of service quality to the satisfaction level of driving license and police certificate applicants had an responses with very satisfied at 48%, satisfied at 50.6%, quite satisfied 1.1%, less satisfied 0.2% , and not satisfied 0.1%. It can be concluded that the driving license and police certificate services at Mataram city resort police, which are carried out by referring to timeliness, adequate infrastructure, and appropriate rates have been able to provide satisfaction for the applicant.